INFLUENCE OF STORAGE TEMPERATURE ON MORPHOLOGICAL AND PHYSIOLOGICAL TRANSFORMATIONS AND SHELF LIFE OF MANGO CV. SUFAID CHAUNSA - KIRAN, S; RAZA, S; BIBI, F; MUSTAFA, G; IQBAL, M; BUKHARI, SIUS; IMRAN, M; IQBAL, A; KHAN, AH; IQBAL, J; MAHMOOD, N; MAJEED, T (Biological and Clinical Sciences Research Journal, 2023)
Mango, scientifically known as Mangifera indica L., is highly popular in Pakistan and around the globe and is known for its abundant provitamins and other phytochemical elements. Being a climacteric fruit, mangoes ripen quickly after being harvested. Commercial growers typically harvest mangoes when they reach their horticultural maturity to maintain the fruit's quality. Temperature is a crucial environmental factor affecting mangoes' quality, as these tropical fruits do not respond well to storage at low temperatures. Therefore, this study aimed to examine the impact of different storage conditions on the physiological and biochemical qualities of the shelf life of cv. Sufaid Chaunsa mangoes. During the study, the mangoes were stored in cold storage facilities at 8°C, 12°C, and 16°C. The storage containers consisted of plastic baskets covered with paper, and the mangoes were assessed for weight loss, texture properties, chilling injury, titratable acidity, sensory characteristics, total soluble salts, and external appearance every 7 days throughout the storage period till 28 days. The results indicated that storing mangoes at 12°C extended their shelf life by up to 21 days, shows better results. Utilizing the storing conditions set at 12°C effectively reduced suitable water loss, maintained chemical changes and other sensory characteristics. Additionally, storing the mangoes at 12°C was sufficient to prolong their storage life until 21 days. It was observed that the quality of mangoes deteriorated after being stored for 21 days at 16°C.